El abastecimiento y consumo responsable de alimentos en Toluca, estado de México - Viesca González, Felipe Carlos; Alvirde Castañeda, Violeta; Espinosa de los Monteros, Gerardo Novo; Quintero Salazar, Baciliza (Tendencias, 2025)
Introduction: In the world there is a serious problem of hunger, malnutrition, food loss and waste, environmental degradation and depletion of natural resources. Objective: To identify food supply habits and some sustainable practices of consumers in Toluca, State of Mexico. Methodology: The field research method used was the survey; a questionnaire was designed as an instrument and applied in the municipality of Toluca to a convenience sample of 281 adults, in the months of September and October 2023 in markets, tianguis and supermarkets. Results: Family spending on food is high; food acquisition and preparation is still a female activity; food is based on vegetables, cereals, meats, eggs; most of them check the refrigerator and pantry before going shopping, and make a shopping list of food before acquiring it. Conclusion: some food supply habits, the profile of responsible and non-responsible consumers were known; food is healthy and responsible food consumption is practiced.